Assessment of the Economic Accessibility of Forest Wood Resources - Aleksandr G. TRETYAKOV; Svetlana S. MORKOVINA; Elena A. KOLESNICHENKO; Mikhail K. DOBROSOTSKY (Communications of International Proceedings, 2024)
The article is devoted to the development and approbation of methodological tools for assessing the economic accessibility of forest wood resources. According to the authors, the assessment of forest wood resources by the criterion of their economic accessibility can become the most effective tool for intersectoral forest planning. The purpose of this article is the theoretical substantiation and development of methodological tools for assessing the economic accessibility of forest wood resources in the system of rational forest management, as well as the formation of directions for including its results in the mechanism of regional forest planning. As a result of the conducted research, the authors have formed a theoretical basis for the concept of assessing the economic accessibility of forest wood resources, including the introduction of a categorical apparatus («economic accessibility of forest wood resources», «accessible», «conditionally accessible/inaccessible» and «inaccessible» forest wood resources) and substantiation for the feasibility of including an assessment of the economic accessibility of forest resources in the forest management planning system. The results of the study can be applied by public administration bodies in the formation of territorial programs for the development of the forest sector of the economy, taking into account the market conditions of forest regional markets. Methodological approaches and tools for assessing the economic accessibility of forest wood resources can be used to determine the amount of payments for forest resources, ensuring a balance of economic interests of the state, forest users and other stakeholders.
Keywords: rational use of resources; forest wood resources; economic accessibility of resources; assessment of economic accessibility of resources